Decoding the Architecture of Molecular Diodes: Rational Design for Ideal Rectification - Sara Gil-Guerrero; Nicolás Ramos-Berdullas; Marcos Mandado (Molecules, 2025)
The design of nanoscale electronic components remains a major challenge because we have limited control over the chemical and physical properties of their molecular constituents. Even subtle structural or compositional modifications can significantly alter their electronic behavior. Consequently, updating a molecular component often necessitates developing a new model from scratch. In this study, we present a comprehensive analysis of the rectification properties of a promising molecular diode initially proposed by Aviram and Van Dyck. The model has been systematically decomposed into fundamental building blocks, enabling the electron transport process to be examined both as an integrated event and as a sum of cooperative interactions. Our findings reveal that certain motifs—such as the D-σ-A architecture—play a significant role in rectification. However, achieving high-performance molecular rectifiers also requires cooperative interplay with other structural elements that contribute to rectification, such as asymmetric molecule–metal contacts. In this study, we conduct a detailed investigation of the roles these elements play in shaping the rectifying characteristics, and we further interpret their effects by analyzing the dominant transport channels under forward and backward bias conditions. This deeper understanding of the transport mechanism offers greater control over the system and opens the door for rational design strategies for improving rectification efficiency in future molecular devices.